Labor Force Entry and Exit by Married Women: A Longitudinal Analysis - Long, James E.; Jones, Ethel B. (The Review of Economics and Statistics, 1980)
In this paper the labor force entry and exit by married women are examined using longitudinal data that enable one to observe actual changes in economic behavior and characteristics. The symmetry assumption is investigated by estimating separate equations for the entry and exit choice. Section II briefly analyzes the wifes labor supply decision and discusses the issue of symmetry. The data and analytical procedure are described in section III and the empirical results are presented in section IV. Some implications of our findings are presented in section V. (excerpt)